Sectarian Insecurities and Terror Driven Violence - Dr. Tehmina Aslam (Corresponding Author); Professor Dr. Muhammad ZIA-UL-HAQ (Journal of Religion and Society, 2025)
In Pakistan, a sectarian conflict is necessarily a post-Partition development. Precisely, in the 1980s, when religion was used to launch a fight against communism which intended to expand its advance south-wards to reach warm waters of the Arabian Sea. The fight engulfed Pakistan, which saw the use of religion to meet one’s objectives. In the meantime, the Iraq-Iran war accentuated the sectarian divide existed within the fold of religion, Islam. Both wars together poured the division into communities living otherwise together peacefully. Further damage in terms of intensity and frequency of violence was done by the war on terror which ran from 2001 to 2021 in the region. Sectarian insecurity is a product of the internecine conflict which has been spoiling religious harmony since the 1980s and got a spike after 2001. Advanced means of war added advanced tactics to the religious discord making terror-driven violence possible. A qualitative research study done on sectarian prone cities in South Punjab such as Sargodha and Jhang came up with certain findings. First, in the region of Central and South Asia, wars in the name of religion wedged open the door of sectarian disharmony, which is refusing to die. Second, from 1980s to 2000s, sectarian disharmony instilled divisions in the domains of political capital and economic resources in South Punjab. Third, the addition of explosive self-controlled jackets, improvised remote-controlled or time-controlled volatile devices and a surfeit of ever-willing suicide bombers, besides target killers, pushed sectarian discord to new limits of terror-driven violence. Fourth, a deep division in the interpreter of religion such as religious and spiritual scholars solidified the grounds taken by religious extremists for perpetual dissonance. Fifth, all efforts of the state to bring about sectarian harmony and sectarian security are still short of brining the society back to the era of peaceful co-existence. Conclusion drawn is that wars fought near Pakistan’s borders affected society adversely, one example of which is sectarian conflict causing now a perpetual disharmony. No doubt, the state of Pakistan has brought the situation under control, sectarian divisions in society have gone deeper than before and may take some years to get healed. Keywords: Sectarianism, Conflict, Shia, Sunni, Religion, Punjab, Pakistan